Timing of immovable property transactions to determine the incidence of tax in South Africa - Juul, Leanne (Department of Finance and Tax, 2017)
The main Acts applicable to the disposal of immovable property are the Alienation of Land Act 68 of 1981, the Deeds Registries Act 47 of 1937(DRA), the Sectional Titles Act 95 of 1986, the Subdivision of Agricultural Land Act 70 of 1970, the Transfer Duty Act 40 of 1949(TDA), the Value Added Tax Act 89 of 1991(VAT Act) and the Income Tax Act 58 of 1962(ITA). Apart from legislation there is also South African common law which is based on Roman-Dutch and English Law principles which also play an important role when dealing in immovable property. This dissertation focuses its review on the timing of immovable property transactions to determine the incidence of tax in South Africa and concentrates on the differences in the timing of ownership according to the ITA, VAT Act, TDA and DRA as well as common law principles. International accounting standards have been reviewed and a comparison drawn between the accounting treatment of a disposal and the tax treatment as well as a comparison drawn up between South Africa and Australia with regards to how for tax purposes the disposal of immovable property is treated. Statutory authority is necessary before taxes can be imposed and only the statute must be used in order to determine the liability for tax. Accounting or related principles are not taken into account when the tax liability is determined except in instances where the ITA specifically provides for it. The aim of this dissertation is to answer the question of whether there is a disconnect between the timing of the transfer of immovable property and the timing of the attendant taxation for the seller through analysing specifically the various Acts and laws which impact the transfer of immovable property.